Annexin A11 (ANXA11) gene polymorphisms are associated with sarcoidosis in a Han Chinese population: a case–control study. Issue 7 (23rd July 2014) - Feng, Xianjun; Zang, Shuzhi; Yang, Yanrong; Zhao, Shasha; Li, Yunxia; Gao, Xinyuan; Zhang, Ligong
Abstract : Objectives: To further identify the single-nucleotide polymorphisms (SNPs) that contribute to the genetic susceptibility to sarcoidosis, we examined the potential association between sarcoidosis and 15 SNPs of the ANXA11 gene. Design: A case–control study. Setting: A tuberculosis unit in a hospital of the university in China. Participants: Participants included 412 patients with sarcoidosis and 418 healthy controls. Methods: The selected SNPs were genotyped using the MALDI-TOF in the MassARRAY system. Results: Statistically significant differences were found in the allelic or genotypic frequencies of the rs2789679, rs1049550 and rs2819941 in the ANXA11 gene between patients with sarcoidosis and controls. The rs2789679 A allele (p=0.00004, OR=1.42, 95% CI 1.17 to 1.73) and rs2819941 T allele (p=0.0006, OR=1.41, 95% CI 1.16 to 1.71) were significantly more frequent in patients with sarcoidosis compared with controls. The frequency of the rs1049550 T allele (p=0.000002, OR=0.61, 95% CI 0.49 to 0.74) in patients with sarcoidosis was significantly lower than that in controls. The multi-SNP model reveals that rs1049550 is the only independent SNP association effect after accounting for the other two marginally associated SNPs. In block 2 (rs1049550–rs2573351), the T–C haplotype occurred significantly less frequently (p=0.001), whereas the C–C haplotypes occurred more frequently (p=0.0001) in patients with sarcoidosis than controls. Furthermore, genotype frequency distribution revealed that, in rs1049550, the CC genotype was significantly more in patients with chest X-ray (CXR) stage I sarcoidosis than in patients with CXR stage II–IV sarcoidosis (p=0.012). Conclusions: These findings point to a role for the polymorphisms of ANXA11 in sarcoidosis in a Chinese Han population, and may be informative for future genetic studies on sarcoidosis.